Electron Beam 조사가 인삼분말의 지방질 안정성에 미치는 영향 - 이미경(Mi-Kyung Lee); 최강주(Kang-Ju Choi); 김정숙(Jeong-Sook Kim); 권중호(Joong-Ho Kwon) (Journal of ginseng research, 2005)
Electron beam (EB), electrically produced from an electron accelerator, was compared with gamma ray (GR) in terms of its influence at doses from 0 to 15 kGy on the lipid stability of white and red ginseng powders. Irradiation (EB or GR) less than 10 kGy showed negligible effects on the composition of fatty acids in white and red ginseng powders. The thiobarbituric acid (TBA) value, however, increased with irradiation doses and storage time in both samples, which was more significant in red ginseng than white ginseng. Red ginseng revealed higher electron donating ability than white ginseng, even though there was insignificant difference between non-irradiated and irradiated samples irrespective of the post-irradiation storage for 4 months under room temperature as well as energy sources applied. 인삼분말의 새로운 살균법을 연구할 목적으로 백삼과 홍삼분말을 대상으로 전자빔과 비교구로써 감마선을 각각 $0\~15kGy$ 범위로 조사시킨 다음, 시료의 지방질 관련 성분에 미치는 영향을 검토하였다. 살균효과가 인정되는 10 kGy이하의 전자빔 및 감마선 조사는 백삼 및 홍삼 분말의 지방산 패턴 및 조성에 영향을 미치지 않았다. 방사선 조사는 시료의 TBA가를 증가시켰으며, 저장기간이 경과함에 따라 모든 시험군에서 다소 증가됨을 보였다. 특히 홍삼분말이 백삼분말보다 높은 TBA가를 나타내었다. 백삼보다 홍삼 시료에서 강한 전자공여능을 나타내었고, 방사선 조사 여부뿐만 아니라 전자빔과 감마선 사이에도 유의적인 차이가 없었다. 한편 저장 4개월 후에도 인삼분말의 전자공여능은 유의적인 변화를 보이지 않았다.